Desigualdades de Sobolev e equações Elípticas não lineares - Costa, Leon Tarquino da (2016)
In this work we first study some interesting generalizations of the famous inequality Sobolev to limited domains. Then, we will study the existence of positive solution for a nonlinear elliptic equation on a certain condition Neumann, by imposing certain restricitive condition in the nonlinearity. To we consider more general hypotheses we will assume conditions on the boundary of domain.